Micro foundations for knowledge spillovers in spatial equilibrium models - Stein Ostbye; Sylvain Barde (European Regional Science Association (ERSA), 2010)
Knowledge spillovers have recently been analysed by Barde (2009) and Ostbye (2010) in a spatial general equilibrium framework. Both studies lack explicit micro foundations for the spillovers - spillovers just take place and depend on firm density. The models must therefore be seen as reduced forms that may potentially be consistent with several structural interpretations. In this paper, the aim is to go some way in offering plausible micro foundations. We consider two alternatives: knowledge dissemination through knowledge embodied in labour moving between firms following Combes and Duranton (2006) and knowledge creation and dissemination through research and development (R&D) following d'Asprémont and Jacquemin (1988).
Keywords: 330; knowledge spillovers